Sarawak the hub of 'HALAL' livestock production : the prospects and challenges - Fabian, Henry (Universiti Malaysia Sarawak (UNIMAS), 2004)
Since Malaysia is an Islamic country, and Sarawak with her vast land that was still under utilized, this could be a good opportunity of turning Sarawak as the leading producer of Halal livestock and livestock related product. The prospects would definitely be the huge market opportunity all around the world for these specialized products, which would help the growth of the stateʼs economy, development and also increase in employment.